In vivo occupancy of the vitamin D responsive element in the osteocalcin gene supports vitamin D-dependent transcriptional upregulation in intact cells. - Breen, E C (1994)
The steroid hormone vitamin D is a principal mediator of skeletal homeostasis. 1,25-Dihydroxyvitamin D3 treatment of ROS 17/2.8 osteoblast-like cells results in a ligand-dependent increase in transcription of the bone-specific osteocalcin gene. This transcriptional upregulation requires the positive cis-acting vitamin D responsive element (VDRE). We have used the ligation-mediated polymerase chain reaction to demonstrate that protein occupancy of the VDRE within the intact cell correlates with increased synthesis of osteocalcin transcripts. These protein-DNA contacts were not present in the absence of vitamin D or in osteosarcoma cells (ROS 24.1) lacking the vitamin D receptor. Our results establish in intact cells the requirement for both ligand- and receptor-dependent occupancy of the VDRE for vitamin D responsive enhancement of osteocalcin gene transcription.